Structural basis to characterise transactivation domain of BRCA1. Issue 1 (2nd January 2017) - Yadav, Lumbini R.; Biswal, Mahamaya N.; Hosur, M.V.; Kumar, Nachimuthu Senthil; Varma, Ashok K.
Abstract : Familial inheritance of breast and ovarian cancer is attributed to mutations discovered in functional domains of BRCA1 gene. BRCA1 is a multifunctional protein responsible for maintaining the genomic integrity and has transcriptional regulatory function encoded in its C-terminal region. The different amino-terminal e extensions to BRCA1 BRCT domain are responsible for transcription activation. However, only BRCA1 BRCT (1649–1859) amino acids have been explored for its structural characteristics. Noting the importance of extended region to the N-terminus of BRCT different regions of BRCA1 which demonstrates maximum transactivation activity has been explored for their structure and functional activity. Secondary and tertiary structural analysis revealed a limited alpha-helical content with well-folded tertiary structure. In silico tools were used to corroborate the in vitro results. Amino acids composition and sequence analysis display a propensity for intrinsic disorder and coiled-coil formation in BRCA1 (1396–1863) (BRCA1-TAD). The results presented in this paper suggest the extreme flexibility in coiled-coil motif might be an important requirement in the establishment of protein–protein interaction networks for BRCA1.